2016
DOI: 10.1155/2016/5186765
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Quality of Life for Adherence to Sublingual Immunotherapy

Abstract: Background. Nonperception of efficacy ranks among the most commonly cited causes for nonadherence to sublingual immunotherapy (SLIT). Quality of life (QoL) in patients is a determining factor influencing adherence. We investigated QoL and adherence separately in SLIT patients at one pediatric practice in Germany. Methods. We conducted a noninterventional, cross-sectional, retrospective, quality-of-life survey among pediatric patients treated with SLIT. QoL was assessed using the generic SF-12 health survey in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Fourth, family members of patients could be enlisted to help patients complete their immunotherapy. Studies have shown that adherence can be improved if patients perceive a good quality of life . Beyond 3–5 years, efficacy can be maintained for a long time .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, family members of patients could be enlisted to help patients complete their immunotherapy. Studies have shown that adherence can be improved if patients perceive a good quality of life . Beyond 3–5 years, efficacy can be maintained for a long time .…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with few reactions, especially the immunotherapy regimens involving the use of one or two main allergens. 10 Lemberg et al 17 observed a significant improvement in the QoL after a year of treatment, a significant improvement in the severity and control of the disease, and a reduction in the number of sick days and days with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting additional result was the observation that SLIT significantly contributed to treatment adhesion. 17 The improved sense of smell associated with the control of other classical symptoms of persistent allergic rhinitis was the other reason behind the study using patient’s own self-evaluation. Katotomichelakis et al 18 used standardized questionnaires with special attention to olfactory functions in 145 patients with persistent allergic rhinitis being treated with SLIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with any medical therapy, the goal of increasing compliance is to increase therapy effectiveness and thus quality of life. A recent study by Lemberg et al demonstrated that SLIT does have a positive effect on multiple quality‐of‐life measures in patients with allergic rhinitis . In the current study, despite noncompliance, 53% of patients reported a substantial improvement in symptoms since beginning therapy, and another 33% reported either a mild or moderate improvement.…”
Section: Discussionmentioning
confidence: 99%